[Report of the] Conference on development and regional cooperation in the CARICOM area - Scott, Noll, ed. (Commonwealth Institute LondonGB, 1986)
Contains edited speeches of emminent Caribbean personalities on socio-economic issues, political aspects, and cultural dynamism and identity of Caribbean life. Discusses inter alia, topics such as trade and industry, tourism, aid, problems of small island states, and the diplomatic role of CARICOM.